2012
DOI: 10.1063/1.3676267
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of type II band alignment in ZnO nanorods/poly(3-hexylthiophene) heterostructures

Abstract: The emission from ZnO nanorods/poly(3-hexylthiophene) (P3HT) heterostructures with type II band alignment has been investigated. The additional emission due to the formation of the heterojunction around 950 nm has been found and attributed to the type II transition related to the recombination of electrons in conduction band of ZnO and holes in highest occupied molecular orbital band of P3HT. The consistency of excitation power density dependent photoluminescence (PL) spectra with the theoretical prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…In order to to ZnO NWs, which is in contrast to the ZnO NW / PCBM interface where the introduction of ZnO NWs has no effect. From photoluminescence measurements, Chan et al showed the occurrence of a radiative emission around 1.3 eV, which was assigned to the type II radiative transition between electrons in the CBM of ZnO NWs that recombine with the holes in the HOMO of P3HT [187]. Tables 5 and 6 and commented in the following sections.…”
Section: Pbs and Binary Sulfides Bulk-heterojunction Quantum Dot Solamentioning
confidence: 98%
“…In order to to ZnO NWs, which is in contrast to the ZnO NW / PCBM interface where the introduction of ZnO NWs has no effect. From photoluminescence measurements, Chan et al showed the occurrence of a radiative emission around 1.3 eV, which was assigned to the type II radiative transition between electrons in the CBM of ZnO NWs that recombine with the holes in the HOMO of P3HT [187]. Tables 5 and 6 and commented in the following sections.…”
Section: Pbs and Binary Sulfides Bulk-heterojunction Quantum Dot Solamentioning
confidence: 98%
“…In the present case the PVA molecules are most likely to get attached to the ZnO NW surface by forming a complex bond with the ionized V Zn defects through weak electrostatic attraction. 123 Other polymers such as polymethyl methacrylate (PMMA), 87 polymerized acrylonitrile (PAN), 117 poly(styrene-co-maleic acid) (PS-co-MAc), 118 polystyrene sulfate (PSS) 118 and poly(3hexylthiophene) (P3HT) 119 were also successfully utilized for the fabrication of NW HS. These HS exhibit significant improvement in photoluminescence (PL) and photocurrent (PC) behaviours.…”
Section: Zno/organic Radial Heterostructuresmentioning
confidence: 99%
“…In organic/inorganic hybrid systems, for instance, their major advantages for optoelectronic applications are seen in the strong light-matter coupling of the organic components, while the inorganic counterparts excel in large carrier mobilities and thus efficient charge-carrier transport as well as small exciton binding energies. [6][7][8][9][10] Prerequisite for that is the lightinduced creation of hybrid or charge-transfer excitons, which exhibit the hole to a large extent on one side of the interface while the excited electron would reside on the other side. [4,5] Type-II alignment, in turn, is favored for a hybrid solar cell where optical absorption of sunlight is expected to directly lead to electron-hole separation.…”
Section: Introductionmentioning
confidence: 99%
“…These properties together with a type‐I level alignment at the hybrid interface would be ideally suited for light‐emitting applications . Type‐II alignment, in turn, is favored for a hybrid solar cell where optical absorption of sunlight is expected to directly lead to electron‐hole separation . Prerequisite for that is the light‐induced creation of hybrid or charge‐transfer excitons, which exhibit the hole to a large extent on one side of the interface while the excited electron would reside on the other side.…”
Section: Introductionmentioning
confidence: 99%